The Influence of Managerial Ownership, Capital Structure, Dividend Policy and Company Size on Company Value (Study on Sri-Kehati Index in 2020-2024) - Fairus Aulia Azzahra Hadian; Desmiza (Indonesian Scientific Publication, 2026)
This research intends to dissect the correlations between firm value and factors such as managerial ownership, capital structure, dividend policy, and company’s size. For the years 2020–2024, this study looks at ten different firms that make up the SRI-KEHATI index, which represents companies with strong sustainability and ethical considerations in the Indonesian capital market. The data used is secondary data obtained from annual reports and financial statements published by companies and the Indonesia Stock Exchange. Panel data regression is the process put into play for the analysis, with the estimation conducted using the Random Effects Model (REM). The results of the study show that managerial ownership and size have a positive impact on the Tobin’s Q, meanwhile the debt to equity ratio and dividend payout ratio do not affect Tobin's Q. Simultaneously, managerial ownership, capital structure, dividend policy, and company size affect the Tobin’s Q. These results show that regular financial choices don't have the same level of interest for investors as things that show a company's sustainability, long term prospects, and future growth potential.